PERAN LEMBAGA AMIL ZAKAT DOMPET DHUAFA DALAM MEMBERDAYAKAN PETERNAK MISKIN DI BANGKALAN - Mar‟atus Sholikah; Suherman Rosyidi (Universitas Airlangga, 2018)
Poverty is a serious problem in Indonesia. As a developing country, the poor inhabitants in Indonesia is still high. According to BPS, shows that 27,7 thousand individu is the poor. Therefore to reduce the problem of poverty, empowerment is one of the right solutions. Especially for poor farmers. Dompet Dhuafa Amil Zakah institution has a empowerment program for the poor farmers, namely “Ternak Berdaya” This study aims to describe the role of Dompet Dhuafa (DD) amil zakat institution in economic empowerment of Farmers in Lantek Temor village, Galis District, Bangkalan City. Using qualitative descriptive approach with study case method, the data collected are donetrough interviews, observation, and documentation. In validating the data, this study uses source triangulation and technique triangulation. Analytical Technique uses descriptive analysis with stages data reduction, presentation, and conclusion. The results of this study indicate that DD has a role in economic empowerment of Farmers as a capital giver from zakah and market network provider, but didn‟t optimal yet. It could be seen through the results of the analysis of four indicators of program success, namely welfare consisting of food, clothing, shelter, and spiritual aspects, increasing income, making it work, and transforming mustahik into muzaki. Among four indicators there are some that have not been met, namely welfare from the spiritual aspect, due to the absence of special religious programs for farmers groups. In addition, the additional income from this program is still relatively small so it can not transform the mustahik be the muzaki of zakah mal. REFERENCESAd-Dymasyqi, A. 2000. Tafsir Ibnu Katsir. Bandung: Sinar Baru Algensindo. Ahmadi, Abu. 1982. Psikologi Sosial. Surabaya: PT. Bina Ilmu.Al-Qur’an, 1989. Departemen Agama R.I, Yayasan Penyelenggara Penterjemah Al-Qur’an Jakarta, Al-Qur’an dan Terjemahannya. Jakarta: CV.Toha Putra SemarangAl-Zuhayly, Wahbah. 1995. Zakat (Kajian Berbagai Mazhab). Bandung: PT Remaja Rosdakarya.Badan Pusat StatistikBerita Resmi Statistik. Profil kemiskinan Indonesia 2016.2017. Jakarta. No. 05/01/Th. XXDivisi Publikasi dan Jaringan Pusat Kajian Strategis (Puskas) BAZNAS.2016. Outlook Zakat Indonesia 2017. Jakarta: Pusat Kajian Strategis Badan Amil Zakat Nasional (BAZNAS)Jaelani, Dian Iskandar. 2014. Pemberdayaan Ekonomi Umat Dalam Perspektif Islam. Eksyar.Vol 01 No 01.Muhammad dan Ridwan Mas’ud. 2005. Zakat dan Kemiskinan Instrumen Pemberdayaan Ekonomi Umat. Yogyakarta: UII Press)Purwana, Eko Agung. 2014. Kesejahteraan dalam Perspektif Ekonomi Islam. Justitia Islamica. Vol. 11/No. 1. Stain Diponegoro Peraturan Pemerintah Republik Indonesia Nomor 14 Tahun 2014 tentang Pelaksanaan Undang-undang nomor 23 Tahun 2011 tentang Pengelolaan Zakat.Rodin, Dede. 2013. Pemberdayaan Ekonomi Fakir Miskin dalam Perspektif Al-Qur’an. Economica vol 6 no 1Shihab, M. 2002. Tafsir al-Misbah. Jakarta: Lentera. Sugiyono. 2011. Metode Penelitian kuantitatif Kualitatif dan R&D. Bandung:Alfabeta Sumartiningsih, Agnes. 2004 Pemberdayaan Masyarakat Desa Meialui Institusi Lokal,Yogyakarta: Pustaka PelajarUndang-undang No. 23 Tahun 2011 tentang Pengelolaan Zakat.Wuryandani, Dewi, dkk. 2015. Mewujudkan Agenda Prioritas Nawacita. Jakarta: Pusat Pengkajian, Pengolahan Data dan Informasi (P3DI) Sekretariat Jenderal DPR RI bersama Azza Grafika, Anggota IKAPI DIYWebsite www.republika.co.idwww.ddjatim.org.